2001
DOI: 10.1021/ic001064d
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Bonding in Hartwig Stretched η3-Hydridoborate σ-Complex of Niobium(III)

Abstract: Ab initio calculations at the SCF, MP2, CASSCF, and CASPT2 levels of theory with basis sets using atomic pseudopotentials have been carried out for the stretched eta(3)-hydridoborate sigma-complex of niobium, [Cl2Nb(H2B(OH)2)], in order to investigate the nature and energetics of the interaction between the transition metal and the eta(3)-hydridoborate ligand. The geometry of the complex [Cl2Nb(H2B(OH)2] and its fragments [Cl2Nb](+) and [H2B(OH)2](-) were optimized at SCF and CASSCF levels. These results are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The adopted coordination mode is thus the result of electronic effects. As expected for a dihydridoborate ligand,5a the Ru−B bond is significantly longer than in 2Bpin and 2Bcat , and its value of 2.346(4) Å is high enough to exclude a dihydride boryl coordination mode 6a. Moreover, the orientation of the BBN (the angle Cent(C1,C1‘)−B−Ru is 177.9°) agrees with a dihydridoborate coordination.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The adopted coordination mode is thus the result of electronic effects. As expected for a dihydridoborate ligand,5a the Ru−B bond is significantly longer than in 2Bpin and 2Bcat , and its value of 2.346(4) Å is high enough to exclude a dihydride boryl coordination mode 6a. Moreover, the orientation of the BBN (the angle Cent(C1,C1‘)−B−Ru is 177.9°) agrees with a dihydridoborate coordination.…”
Section: Resultssupporting
confidence: 64%
“…The past decade has seen major conceptual advances in the field of borane activation . Landmark findings have been disclosed both in fundamental aspects of coordination chemistry and in catalysis. Several reports have shown that boron-containing moieties can adopt several geometries when bound to both early- and late-transition-metal centers 6 that also support hydride ligands (see Figure ). Better knowledge has been gained on the properties of transition-metal boryl compounds,6a and isolation of a few σ-borane complexes has been achieved following the first report in 1996 by Hartwig et al These two classes of compounds play a central role in key events in catalysis, such as B−H oxidative addition and reductive elimination steps.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of the B−H interactions in hydridoborate complexes depends on the substituents at boron. The B−H interaction in a hydridoborate structure with π-donating alkoxide groups on boron is much weaker than the B−H interaction in a hydridoborate structure lacking a π-donor group on boron. , In fact, the experimental and theoretical studies on the structure of complex 2 imply that there is a significant interaction of the dialkoxyboryl group with only one of the two hydride ligands. As a result of the weak B−H interaction involving a second hydride and a boryl group with alkoxo substituents, the barrier for isomerization of the complex with mutually trans methyl and dialkoxyboryl groups to a complex with mutually cis methyl and dialkoxyboryl groups is low.…”
Section: Resultsmentioning
confidence: 99%
“…Ab initio calculations have been performed for r-borane complexes [(g 5 -C 5 H 5 )Ti{H-B(OH) 2 } 2 ] and [(g 5 -C 5 H 5 )Ti{HB(H) 2 r-borate complexes [(g 5 -C 5 H 5 ) 2 Nb{H 2 B(OH) 2 }] [42], [(g 5 -C 5 H 5 )Nb{H 2 B(C 8 H 14 )] and [(g 5 -C 5 H 5 )Nb{H 2 B(H) 2 }] [43].…”
Section: Introductionmentioning
confidence: 99%